Über Braconiden (Hymenoptera) aus dem Deutschen Entomologischen Institut. - Belokobylskij, Sergej A. (Contributions to Entomology = Beiträge zur Entomologie, 1995)
Two new species are described: Hormius antefurcalis sp. n. (Germany) and Colastes (Colastes) taegeri sp. n. (Mongolia). Procrisis acutus Tobias is recorded from Germany for the first time. Cenocoelinus koshuneusis Watanabe, 1934 is transferred into the genus Ussurohelcon Belok. A key to the species of Ussurohelcon is given. Nomenclatural Acts taegeri Belokobylskij, 1995 (Colastes (Colastes)), spec. n. antefurcalis Belokobylskij, 1995 (Hormius), spec. n. koshunensis (Watanabe, 1934) (Ussurohelcon), comb. n. hitherto Cenocoelius koshunensis